Exploring the floristic diversity of tropical Africa - Sosef, M.S.M.; Dauby, G.; Blach-Overgaard, A.; Burgt, X. van der; Catarino, L.; Damen, T.; Deblauwe, V.; Dessein, S.; Dransfield, J.; Droissart, V.; Duarte, M.C.; Engledow, H.; et al. (Springer, 2017)
Background Understanding the patterns of biodiversity distribution and what influences them is a fundamental pre-requisite for effective conservation and sustainable utilisation of biodiversity. Such knowledge is increasingly urgent as biodiversity responds to the ongoing effects of global climate change. Nowhere is this more acute than in species-rich tropical Africa, where so little is known about plant diversity and its distribution. In this paper, we use RAINBIO – one of the largest mega-databases of tropical African vascular plant species distributions ever compiled – to address questions about plant and growth form diversity across tropical Africa.